MICHELA BAROSIO ET AL. - Architecture’s Afterlife. The Multisector Impact of an Architecture Degree - Delgado Orusco, Eduardo (ZARCH, 2025)
MICHELA BAROSIO, DAG BOUTSEN, ANDREA ČEKO, HAYDEE DE LOOF, JOHAN DE WALSCHE, SANTIAGO GOMES, HARRIET HARRISS, ROBERTA MARCACCIO, MIA ROTH-ČERINA, CARLA SENTIERI, NEAL SASHORE, FEDERICA VANNUCCHI Y HANNE VAN REUSEL Architecture’s Afterlife. The Multisector Impact of An Architecture Degree Routledge. New York, 2024, 204 pp. Tapa dura. 45 € Idioma: inglés ISBN-10: ‎ 103253334X ISBN-13: ‎ 978-1032533346